Cuproplasia characterization in colon cancer assists to predict prognosis and immunotherapeutic response - Zhang, Bomiao; Li, Yien; Song, Liqiang; Xi, Hua; Wang, Shaoke; Yu, Chenfeng; Cui, Binbin (Frontiers in Oncology, 2023)
Colon cancer is the 3rd most prevalent cancer worldwide, with more than 900,000 deaths annually. Chemotherapy, targeted treatment, and immunotherapeutic treatment are the three cornerstones of colon cancer treatment; however, the occurrence of immune therapy resistance is the most pressing problem to solve. Copper is a mineral nutrient that is both beneficial and potentially toxic to cells and is increasingly implicated in cell proliferation and death pathways. Cuproplasia is characterized by copper-dependent cell growth and proliferation. This term encompasses both neoplasia and hyperplasia and describes the primary and secondary effects of copper. The connection between copper and cancer has been noted for decades. However, the relationship between cuproplasia and colon cancer prognosis remains unclear. In this study, we applied bioinformatics approaches to delineate cuproplasia characterization of colon cancer, set up a robust Cu_riskScore model based on cuproplasia-relevant genes and found its relevant biological processes, including immune response and chemokine signaling. Finally, we tried to find an association between immunotherapy and Cu_riskScore.